Impact of Agricultural exploitation and duration in the Use on some elements nutrients Some of the soil of Al-Qasim Denatore - AL – Kurayshi, Amal Radhi Jubier; Jasim, Eiman Asmaiel (Journal of Kerbala for Agricultural Sciences, 2018)
Selected soils located in Al-Qasim area in the southern part of the province of Babylon between latitudes 23̊09̍02.69̎ N to 32̊26̍36.04̎ N north and longitudes 44̊23̍41.97̎ E to 44̊48̍52.69̎ E East 7is selected at the Fayadieh area 3053.5 hectare. Alpedons coordinates were determined using a GPS and selected on the basis of differences in agricultural exploitation period. Pedon is selected in the soils used for 5,10 and 15 years. These are compared with that of untapped agricultural soils. This revealed the pedonat and described its prospects was dogmatic morphology description obtain samples from all horizons and study fertility properties . the results Showed fertility Properties Statistical analysis of nitrogen, phosphorus and potassium than primers used for duration (5 years) Morally sxploited for Soil ( 10-15 years),and there were no moral differences of nitrogen Content between phosphorus duration ( 5 years ) and Soil bare (agricultural land unused ) but overtook the moral treatment of Soil bare potassium soil Content under durations (5 ,10 ,15 years ) due to contenuosagriculture have low potassium Content ready as well as the influence of Soil Salinity increasing potassium Content in Soil bare. Soil was Classified as Studied by American Classification (2010) Classify Series AL. Agidi (1976 ), Classified all the exploited agricultural land unused (bare ) to the order of Entisosls if Classified Subgroup TypicTorrifluvents, Soil Classification Series Alagidi were as follows: TW1176,TW1167,TM855,DM86,DW116,DW56,MW11.